Efektivitas Pelayanan Kesehatan di Puskesmas Jumpandang Baru Kota Makassar - Tetty Dwiyanti; Adina astari (Pascasarjana STIE Amkop Makassar, 2020)
AbstractPuskesmas Jumpandang Baru Makassar City. This study aims to obtain a picture of the effectiveness of health services at Puskesmas Jumpandang Baru Makassar City and to know the factors that affect the effectiveness of health services at Puskesmas Jumpandang Baru Makassar City. To answer the problem of research, used descriptive research method with qualitative approach. Data collection is done by observation, interview and documentation. In addition, data collection also uses data analysis techniques by collecting, data reduction, data presentation and conclusions. The effectiveness of health services at Puskesmas Jumpandang Baru Makassar City is in accordance with indicators used to measure the effectiveness of health services such as achievement of goals, integration, adaptation, and commitment Factors that influence the effectiveness of health services in Puskesmas Jumpandang Makassar City such as organizational characteristics, environmental characteristics, worker characteristics and managemant characteristics. Keywords: Effectiveness and management